Modelling energy metabolism of friesians in Kenya smallholdings shows how heat stress and energy deficit constrain milk yield and cow replacement rate - King, J.M.; Parsons, D.J.; Turnpenny, J.R.; Nyangaga, J.; Bakari, P.; Wathes, C.M. (Cambridge University Press, 2006)
The 2002 World Summit on Sustainable Development focussed attention on agricultural sustainability and biodiversity in developing countries. These goals are relevant for livestock production in Kenya, where development agencies encourage resource-poor smallholders to acquire large, exotic, high-yielding dairy cows, despite their poor performance, revealed in recent surveys in the highlands and at the coast. The performance of the cows is not in question. The debate relates to the diagnosis of the causes, their treatment and the prognosis for the production system. To improve our understanding of the dynamics of the system, models of nutrition and energy, modified for the tropics, were used to measure the thermal responses over 24 h of six pure or crossbred Friesians at a mean lactation of 54 (s.d. 21.6) days, in separate zero-grazing units. Four smallholdings were on the hot, humid coast and two in the cooler highlands. The output of the model runs was related to the subsequent lactation, calving interval and profitability of the cows. The model showed that the thermal load caused moderate stress for all cows during the day, which became severe in the sun in the highlands, but the drop in air temperature, from 27ºC to 13ºC, at night dissipated the gain in body heat. At the coast, where the air temperature remained above 24ºC and relative humidity above 0.85, there was no remission of heat stress for cows with a milk yield greater than 11 l/day. The lactation curve, in all cows, declined from an initial peak to a low profile of 5 l/day. Cows in both regions with initial yields above 20 l/day had the steepest decline and longest calving intervals (457 to 662 days). They had the largest lactation yields and lowest direct cost per litre, but their poor breeding record reduced cull sales and increased replacement cost, raising the total cost per litre. By contrast, the cow with the lowest daily and lactation yield had the highest direct cost, but lowest total cost per litre, because she produced 2 heifer calves at an interval of only 317 days. These case studies serve as a reminder that, where heat load depresses appetite or poor food cannot support lactation, the energy deficit and stress reduces cow fertility, fitness, and longevity, so that she fails to breed a heifer replacement during her shortened productive life. The model predicted that food intake, depressed by heat stress, would not support a milk yield above 14 l/day and 3000 l per annum at the coast, and 22 l/day and 5000 l per annum in the highlands. Therefore, although appearing profitable in the short term, the current policy of promoting cows with higher yields than the climate and production system can support, is unsustainable. This outcome has implications for smallholder dairy development policy in Kenya, and probably elsewhere in the tropics. Instead one should reconsider smaller exotic breeds and crossbreds with improved indigenous dairy cows whose overall productivity from milk yield, fecundity, longevity, and disease tolerance 50 years ago was better than that of the modern Holstein-Friesian in a Kenya smallholding.